2022
DOI: 10.1038/s41467-022-35160-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable neuromorphic memristor network for ultralow-power smart textile electronics

Abstract: Neuromorphic computing memristors are attractive to construct low-power- consumption electronic textiles due to the intrinsic interwoven architecture and promising applications in wearable electronics. Developing reconfigurable fiber-based memristors is an efficient method to realize electronic textiles that capable of neuromorphic computing function. However, the previously reported artificial synapse and neuron need different materials and configurations, making it difficult to realize multiple functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 50 publications
0
61
0
Order By: Relevance
“…Device functioning as detailed above consumes only ∼1.06 pJ per synaptic junction (see Note S1, ESI†), which is comparable to the reported values from other neuromorphic devices. 40,41…”
Section: Resultsmentioning
confidence: 99%
“…Device functioning as detailed above consumes only ∼1.06 pJ per synaptic junction (see Note S1, ESI†), which is comparable to the reported values from other neuromorphic devices. 40,41…”
Section: Resultsmentioning
confidence: 99%
“…Textiles are another form factor that holds great promise. Many advanced functions have been demonstrated on textile platforms, and integrated systems can achieve energy harvesting, energy storage, sensing, display, and simple signal processing. ,, Furthermore, industrial scale or industry-compatible production has been reported, ,,,, and commercial products have started to emerge . Smart textiles might not be far from large-scale deployment.…”
Section: Sensor-biology Interfacementioning
confidence: 99%
“…Currently, fibers and textiles with sensing, energy supply, and actuation capabilities have become popular research topic. , Unlike conventionally postassembled wearable devices, fiber-shaped devices can be assembled during fabric production . This one-step formation technique guarantees the overall comfort and mechanical properties of the fabric . Moreover, various topologies based on the weaving process permit flexible arrangement and more effective connecting of fiber devices, thereby improving the unit area density and working efficiency of the device .…”
Section: Applications and Devicesmentioning
confidence: 99%
“…23 This one-step formation technique guarantees the overall comfort and mechanical properties of the fabric. 177 Moreover, various topologies based on the weaving process permit flexible arrangement and more effective connecting of fiber devices, thereby improving the unit area density and working efficiency of the device. 177 The key to the development of all-fabric flexible wearable systems is the incorporation of logic computing functions into fibers and textiles.…”
Section: Organic Field Effect Transistorsmentioning
confidence: 99%
See 1 more Smart Citation